The Evolution of Media Narratives on Ukrainian Refugees in Poland (2022–2024): from Solidarity to Tension and Shifting Public Trust - Batko, Kornelia; Turska, Elżbieta; Tatarczyk, Dawid (Horyzonty Polityki, 2025)
RESEARCH OBJECTIVE: This article examines how Polish media narrate issues related to Ukrainian refugees and how these narratives evolve over time alongside political, social, and economic developments. Our analysis covers the first two years of the Russia-Ukraine conflict, from February 2022 to February 2024.THE RESEARCH PROBLEM AND METHODS: Our research utilizes qualitative content analysis to identify dominant frames, themes, and discursive strategies used by the newspapers, focusing on two of Poland’s most influential newspapers: Gazeta Wyborcza and Rzeczpospolita. The article outlines changes in the media narratives and situates them within changing contextual conditions, without assessing audience reception or public perception.THE PROCESS OF ARGUMENTATION: The argument proceeds in three steps: (1) it situates media discourse within the broader theoretical framework of trust, migration, and media framing, outlining how symbolic narratives are constructed during humanitarian crises; (2) it compares the coverage of both newspapers, mapping the transformation of refugee-related narratives across political and economic contexts; and (3) it examines how shifts in media framing correspond with broader societal and political developments observed during the same period, without drawing conclusions about their mutual influence.RESEARCH RESULTS: Initially, both outlets framed the refugee influx through humanitarian solidarity, highlighting shared history and moral responsibility. Over time, however, narratives began to emphasize challenges related to welfare strain, labor competition, and social cohesion. This change intensified during politically sensitive moments—such as the 2023 grain crisis—when public debate focused on national resources and solidarity fatigue. These developments signaled a shift toward more ambivalent or issue-focused portrayals of refugees and unfolded alongside broader societal tensions of the period.CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: The study shows that media outlets function not merely as transmitters of facts but as co-creators of social trust and collective meaning. By revealing the mechanisms through which trust is built and destabilized, the article contributes to understanding the politicization of humanitarian crises and offers insights for more balanced media communication.